Job Security and Liquid Wealth - Ana Figueiredo; Olivier Marie; Agnieszka Markiewicz (Institute of Labor Economics (IZA), 2024)
We study changes in job security after displacement and exploit eligibility rules for lump-sum payments in the Netherlands to investigate the role of liquid wealth. Within five years of job loss, the likelihood of being in permanent employment remains 12% lower for displaced workers. Those eligible to a lump-sum transfer experience a significantly smaller negative shock to job security. This effect is driven by workers with low liquid wealth, pointing to liquidity constraints as an important mechanism linking unemployment and job security. Finally, we estimate that losses in job security can explain a fifth of the wage cost associated with job displacement.
Keywords: D31; E24; J31; J63; J64; J65; 330; job loss; liquid and illiquid wealth; job security; severance pay; The Netherlands